FRI0209 EFFECTS OF ADD-ON METHOTREXATE IN POLYMYALGIA RHEUMATICA PATIENTS: A RETROSPECTIVE STUDY. (2nd June 2020) - Marsman, D.; Bolhuis, T.; Den Broeder, N.; Van den Hoogen, F.; Den Broeder, A.; Van der Maas, A.
Abstract : Background: Guidelines on polymyalgia rheumatica (PMR) recommend early introduction of methotrexate (MTX), especially in patients with worse prognosis such as flare or glucocorticoid (GC)-related adverse events (AE). 1 GC-AE are reported in up to 65% of PMR patients, 2 and 50% of secondary care patients are unable to discontinue GCs, emphasizing the need for GC-sparing agents. 3 However, evidence regarding MTX efficacy in PMR remains limited. 2 Objectives: To assess the efficacy of add-on MTX in preventing subsequent flares and GC- sparing in PMR patients. Methods: In a retrospective cohort of newly diagnosed PMR patients visiting our hospital from April 2008 - January 2018, patients starting methotrexate (index event) were compared to first-time flaring PMR patients in whom MTX was not started (control group). Concomitant inflammatory rheumatic diseases were excluded. Data on patient, disease and treatment characteristics were compared. Main outcomes were difference in number of subsequent flares per year between groups (multivariable Poisson regression) and mean GC-use (total GC-dose/total follow-up; multivariable linear regression). In the MTX group only, also incidence rate ratio of flare before vs. after starting MTX was assessed. Results: Of 454 PMR patients, 262 were selected; 42 receiving MTX and 220 in the control group. Reasons for prescribing MTX were GC ineffectiveness and/or GC-related AE and MTX starting dose was 10, 15 and 25 mg/week in 11 %, 82% and 2% respectively. Adjusted for covariates, mean GC-use was 1.21 higher in the MTX group compared to the control group (p = 0.155). The yearly incidence rate of flares in the MTX group did not differ from the control group: incidence rate ratio (IRR) 0.93, (95% CI 0.53-1.63). The yearly flare rate was 1.19 before and 0.42 after MTX initiation, resulting in an IRR of 0.36 (95% CI 0.24-0.53). Conclusion: MTX is infrequently prescribed in daily clinical practice, despite guideline recommendations. No difference in GC use or flare incidence was seen between MTX treated patients and controls, although within MTX treated patients, flare rates were lower after MTX start. Confounding by indication may explain the lack of difference in the outcomes between groups. The optimal timing and dosage of MTX in PMR remains unclear, justifying a clinical trial. References: [1]Dejaco C. e.al. 2015. Recommendations. management.of.polymyalgia.rheumatica:a.European.League.Against Rheumatism/American.College.of.Rheumatology.collaborative.initiative.ARD.2015;74:1799-1807. [2]L.Couvaras.etal.Prevalence.of.long-term.steroid.therapy:French data.AB1141 (2017) [3]González-Gay MA et al. Polymyalgia. rheumatica. Lancet. 2017 Oct 7;390(10103):1700-1712 Disclosure of Interests: None declared